2011
DOI: 10.4209/aaqr.2011.03.0024
|View full text |Cite
|
Sign up to set email alerts
|

Identification the Content of the Windbox Dust Related to the Formation of PCDD/Fs during the Iron Ore Sintering Process

Abstract: This study measured the contents of the ionic and elemental constituents, and the chemical compounds containing in windbox (WB) dusts collected from a commercial iron ore sintering plant, then the results were used to identify possible PCDD/Fs formation pathways in the WB. We found that the abundance in both KCl and NaCl may provide a suitable condition for de novo synthesis of PCDD/Fs in the WB. Al, Fe, K, Ca, and Pb were the top five contents in WB16 dusts, but the co-existence of the above five metal conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…The raw material can contain substances that have been reported to be essential or facilitate the formation of PCDD/Fs e.g., chlorine, organic compounds and metal catalysts like Cu (Cieplik et al, 2003). However, though the current understanding is that PCDD/F are majorly formed within the sinter bed, an analysis of the dust particles in wind boxes revealed that it contains significant amounts of Cl and unburnt carbon (Tsubouchi et al, 2006;Kuo et al, 2011) making it a potential area for PCDD/F formation. The contribution from each region to the total PCDD/Fs emitted is still not fully investigated and understood.…”
Section: Pcdd/f Emissions From Sintering Plantsmentioning
confidence: 99%
“…The raw material can contain substances that have been reported to be essential or facilitate the formation of PCDD/Fs e.g., chlorine, organic compounds and metal catalysts like Cu (Cieplik et al, 2003). However, though the current understanding is that PCDD/F are majorly formed within the sinter bed, an analysis of the dust particles in wind boxes revealed that it contains significant amounts of Cl and unburnt carbon (Tsubouchi et al, 2006;Kuo et al, 2011) making it a potential area for PCDD/F formation. The contribution from each region to the total PCDD/Fs emitted is still not fully investigated and understood.…”
Section: Pcdd/f Emissions From Sintering Plantsmentioning
confidence: 99%
“…In addition, the total PCDD/F I-TEQ emissions had adverse health effects on employees in the affected workplaces during the treatment process (Wang et al, 2003a;Wang et al, 2010a). Moreover, the Waelz process increased the fraction of low-chlorinated congeners, because it is more difficult to decompose the aromatic rings of PCDD/Fs than to dechlorinate from the high-chlorinated congeners to the lower ones Li et al, 2007c;Li et al, 2008;Shih et al, 2008;Shih et al, 2009;Yu et al, 2010;Chiu et al, 2011;Kuo et al, 2011). Therefore, the PCDD/F formation, emission, transportation, reduction and risk assessment for the Waelz process need to be evaluated, (Huang et al, 2011), and to treat EAF fly ash needs to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on PCDD/F emissions in thermal reaction facilities, including sinter plants, electric arc furnaces, secondary aluminum smelters, coal-fired power plants, and crematories (Rappe, 1992;Wang et al, 2003a;Wang et al, 2003c;Chen et al, 2004;Lee et al, 2004;Lee et al, 2005;Lin et al, 2007;Lin et al, 2010;Chen et al, 2011;Chiu et al, 2011;Kuo et al, 2011). Generally, the combustion temperature and chlorine content of raw materials plays an important role in PCDD/F formation (Lee et al, 2003;Wang et al, 2003b;.…”
Section: Introductionmentioning
confidence: 99%